Religious Cult Affairs Council in 1940-1950s: Countering Reduction - Zh. V. Akhmadullina (Научный диалог, 2023)
The article explores the experience of establishing state bodies in the Soviet Union that were involved in building relationships with religious organizations. It examines the relationship between the leaders of the Council for Russian Orthodox Church Affairs (CROCA = rus. SDRPC, established in the fall of 1943) and the Council for Religious Cults Affairs (CRCA = rus. SDRK, established in the spring of 1944). The main sources of research are materials from the central archives of Russia. It is reported that Colonel G. G. Karpov was the chairman of SDRPC, while Colonel I. V. Polyansky was the chairman of SDRK. Both chairmen simultaneously served in state security agencies: G. G. Karpov remained the chief for I. V. Polyansky in the Committee for State Security (KGB) for many years, which led to mutual resentment and personal animosity. Archive documents contain information that G. G. Karpov initiated the merger of SDRPC and SDRK. He proposed creating a new organization based on them, which would perform an important task for the Soviet state in building a secular society, and hoped to lead it. The main directions of the struggle to preserve the Council for Religious Cults Affairs are highlighted. Archive data is provided on the measures taken by G. G. Karpov, although he did not succeed in implementing his idea. As time has shown, G. G. Karpov’s proposal for the merger of SDRK and SDRPC was implemented, but much later, in 1965.